ASSESSMENT OF THE ECOLOGICAL STATE OF WATER OF LAKE ISSYK-KUL BY TROPHIC STATE INDEX (TSI) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Implementation of complex assessment of the ecological state of water of LakeIssyk-Kul and development of effective measures and recommendations on preservation of ecological balance of the lake ecosystem is an actual task of scientists of ecologists of the country. Thecountry has long-term monitoring analyses, but there is a need for their processing and carryingout predictive analyses. One of such techniques is the index of trophic level of lake water. Analyses have shown that the trophic status of the lake is subject to temporal and spatial changes. Ingeneral, the lake belongs to oligotrophic water body by trophic status, where the main biogenicelements are low and do not exceed MAC in water. But, according to the trophic state index, c.Chok-Tal is assessed as the most polluted region, in the study sites of Balykchy, Cholpon-Ata,Grigorievka and Bosteri there is a change in the trophic state of aquatic ecosystems from oligotrophic to mesotrophic. This indicates an increase in the concentration of nutrients such as nitrogenand phosphorus in aquatic systems. The use of the trophic state index allows assessing the waterquality of the lake in a more detailed and comprehensive manner and is recommended for its wideapplication by both industrial and research workers.
Keywords: eutrophication, ecological assessment of ecosystems, sustainable development, trophic status, pollution of water bodies.